Detection of Cocaine and Metabolites in Bone Following Decomposition Using 2D LC–MS-MS. Issue 4 (28th December 2017) - Mella, Malorie; Schweitzer, Brendan; Mallet, Claude R; Moore, Tara; Botch-Jones, Sabra
Abstract: Introduction: In forensic toxicology, challenges exist with quantification analysis of cocaine and metabolites in postmortem samples following extensive decomposition. Alternative matrices, such as bone could prove useful when other specimens are not available. Detection and quantification of drugs in complex matrices require time-consuming extraction processes. The objective of this study was to develop a robust extraction and clean-up methodology to efficiently extract cocaine, and its metabolites, in bone and reach target limits of detection using multidimensional chromatography. Materials and methods: Under an Institutional Animal Care and Use Committee protocol, rat specimens underwent a 10–12 weeks chronic intravenous self-administration of cocaine with average daily dosages ranging 13–19 mg/kg. This was followed by a 6-week period of abstinence, followed again by a 3-week period of cocaine self-administration before being euthanized. Fourteen cocaine positive rats were placed at the Boston University Forensic Anthropology Outdoor Research Facility (Holliston, MA, USA) for a period of 12 months. Skeletal remains were collected for testing as well as drug-free control rats. After homogenization of whole bones, the extraction process was performed using a mixed mode reversed-phase/ion exchange sorbent with an extraction time of 1 h followed by analysis using a 2D liquid chromatography–mass spectrometry-mass spectrometry which allowed for direct injection of the eluent without evaporation or reconstitution. The analysis was performed using 100 μL of the final methanol extracts. Results: The limit of quantitation for cocaine and benzoylecgonine was measured at 0.05ng/g and for ecgonine methyl ester it was 0.1ng/g. The analytical method for cocaine gave a linear dynamic range of 0.05–10ng/g with an R 2 = 0.998. Conclusions: The microextraction protocol combined with a multidimensional chromatography used in this study decreased sample preparation time without sacrificing the quality seen with current single dimension chromatography techniques.